Tuberculosis verrucosa cutis in a patient with keloid over ear lobule. (10th July 2013) - Halim, Muhammad Sohail; Ahmed, Sadaf Qadeer; Junaid, Montasir; Bashir, Muhammad Rizwan
Abstract : Tuberculosis (TB) is a global health problem with predominance in resource-poor countries. Extrapulmonary TB constitutes approximately 10% of the cases and can present as different forms depending on the route of entry. Cutaneous TB is a small subset of the extrapulmonary TB. Cutaneous TB can either be of primary origin or secondary origin or it can be a part of a systemic infection. TB verrucosa cutis (TBVC) is the exogenous reinfection of TB in a previously sensitised patient. Routine cultures do not have a high yield in TBVC due to the paucibacillary nature of the organism. Here we are presenting a rare case of a patient who developed in a keloid over the right ear lobule following ear piercing. This has only been presented once in the previous literature and for the first time in the head and neck region.